Observing Others’ Gaze Direction Affects Infants’ Preference for Looking at Gazing- or Gazed-at Faces - Ishikawa, Mitsuhiko; Itakura, Shoji (Frontiers in Psychology, 2018)
Eye gaze is an important signal in social interactions, and it plays an important role to understand what others looking in joint attention situations. Joint attention has been examined in situations involving two people gazing at objects; however, ecologically, infants observe not only faces that gaze at objects but also those that gaze at other people. Here, we examined how eye gaze directed towards another face affect face preferences in infants. A total of 19 children were observed during a joint attention situation and a no-joint attention situation. In the joint attention situation, an adult face in the central position of the screen shifted her gaze to look at another adult face at a lateral position on the screen. However, during the no joint attention situation, the central face shifted her eye gaze away from the adult face presented on the screen. At test, for the centrally presented faces, infant looking times were longer at faces in the no joint attention condition. At test, for the laterally presented faces, looking times were longer at the faces in the joint attention condition. Thus, the adult’s eye gaze biased the duration of the gaze of the infants at either the central faces or the lateral-cued faces in the preferential looking tests. These results suggest that ten-month-old infants may interpret adult gazing behavior and that this can affect the gazing behavior of infants.